Konstrukce jednoúčelové pily - Rakhmatullin, Artem (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2023)
Tato diplomová práce se zaměřuje na návrh jednoúčelové pily pro vyřezání drážek na hliníkových profilech. Práce zahrnuje zkoumání různých typů pil, zkoumání různých konstrukčních alternativ, identifikaci a výběr nejvýhodnější varianty, následné vytvoření detailního návrhu na základě zvoleného řešení a komplexní vyhodnocení výsledného návrhu. Požadovaným výsledkem je design pily, který upřednostňuje faktory, jako je ergonomický komfort, bezpečnost, přesnost a provozní efektivita, a zajišťuje tak ucelené a efektivní řešení.

This thesis focuses on the design of a single-purpose saw for cutting grooves on aluminum profiles. The work includes the examination of different types of saws, the examination of various design alternatives, the identification and selection of the most advantageous variant, the subsequent creation of a detailed design based on the chosen solution and a comprehensive evaluation of the resulting design. The desired result is a saw design that prioritizes factors such as ergonomic comfort, safety, precision and operational efficiency, ensuring a complete and efficient solution.
A design of single-purpose saw
Keywords: Jednoúčelový stroj; pila; hliníkové profily; multikriteriální analýza; konstrukce.; Single-purpose machine; saw; aluminum profiles; multicriteria analysis; construction.